Heterologous expression of Zn-binding peptide RaZBP1 from Russula bresadolae does not overcome Zn and Cd detoxification mechanisms in Hebeloma mesophaeum - Beneš, Vojtěch; Leonhardt, Tereza; Kaňa, Antonín; Sácký, Jan; Kotrba, Pavel (Folia microbiologica, 2019)
Homeostatic mechanisms preventing the toxicity of heavy metal ions in cells involve, among others, compartmentalization and binding with peptidaceous ligands, particularly the cysteinyl-rich metallothioneins (MTs). We have previously shown that in natural conditions Zn-overaccumulating ectomycorrhizal (EM) fungus Russula bresadolae stores nearly 40% of Zn bound with cysteinyl- and hystidyl-containing RaZBP peptides, which resemble MTs, while the detoxification of Zn and Cd in EM Hebeloma mesophaeum relies upon compartmentalization in small vesicles and vacuoles, respectively. Here, we examined the performance of RaZBP1 gene expressed in H. mesophaeum mycelium with respect to handling of Zn and Cd. Expression of RaZBP1 impaired growth of the mycelium on low-Zn medium by 60%, the growth was partly ameliorated upon the addition of Zn and remained considerable up to 2 mmol/L Zn, while the growth of the wild-type and control mycelia transformed with empty T-DNA was severely reduced in the presence of 0.5 mmol/L Zn; furthermore, RaZBP1 slightly added to Cd tolerance in the range of Cd concentrations of 0.625 to 8 μmol/L. Staining of Zn- or Cd-exposed hyphal cells with Zn- or Cd-specific fluorescent tracers did not indicate that the expression of RaZBP1 would redirect the flow of the metals away from their innate sinks. Size exclusion chromatography of extracted metal species revealed that the complexes corresponding to Zn/Cd-RaZBP1 are present only in minute levels. Considering that RaZBP1 inhibited growth at low Zn, and despite the benefit that it provided to H. mesophaeum in the presence of high Zn and moderate Cd, these data indicate that the binding of excess Zn and Cd with RaZBP1 is not a trait that would be outright transmitted to H. mesophaeum.
Keywords: Basidiomycota; mycelium; Cytoplasmic Vesicles; metalothionein; Mycorrhizae; Mycelium; rekombinantní proteiny; zinek; Fungal Proteins; Metallothionein; Recombinant Proteins; kadmium; cytoplazmatické vezikuly; mykorhiza; Zinc; fungální proteiny; Hebeloma; Cadmium